Analisis Komparatif Efektivitas dan Kontribusi Pajak Reklame Kabupaten Kebumen dan Kabupaten Purworejo Tahun 2017-2019 - Wulandari, Akfila; Mahardhika, Arya Samudra (Jurnal Ilmiah Akuntansi Kesatuan, 2021)
The study aimed to determine the comparative (comparison) effectiveness and contribution of advertisement tax in Kebumen Regency and Purworejo Regency in 2017-2019. The research method used was quantitative descriptive by using secondary data obtained from the Directorate General of Balance and Finance, Ministry of Finance (DJPK) in the form of billboard tax target data, billboard tax realization, and realization of local revenue (PAD). The analysis used in this study using the ratio of effectiveness and contribution. The results of the research on advertisement tax in Kebumen Regency and Purworejo Regency in 2017-2019 showed that the effectiveness level of the advertisement tax was included in the very effective criteria with an average of 165,07% Kebumen Regency and 161,67% of Purworejo Regency while the contribution of advertisement tax to Regional Original Income (PAD) has the criteria of relatively not contributing with an average of 0,16% Kebumen Regency and 0,20% Purworejo Regency. The comparison of the level of effectiveness shows that Kebumen Regency has a superior level of effectiveness than Purworejo Regency. The large comparison of contributions shows that Purworejo Regency is superior in terms of contribution than Kebumen Regency.